THE UNIVERSITY STUDENTS’ ACHIEVEMENT ON TOEFL-LIKE TEST - Ashari, Mr; Nugroho, Agus Sapto (Jurnal Bahasa Inggris, 2017)
Ideal English teachers are those who have no longer problems with English. Therefore, having good competence of English is a must for English teacher candidates. TOEFL is one of the tests to measure the competence. The aims of this research are to find out the maximum score of TOEFL PREDICTION achieved by the students of S1 English Education Program, Academic Year 2016/2017 and to find out the lowest score of the test component achieved.The kind of this research is descriptive. The data collection was conducted by applying Total Sampling Technique. The instrument of this research was TOEFL PREDICTION TEST (paper based). The test is scored on a scale of 217 to 677. The finding of the research shows that there is no respondent who can achieve the high score (0%). Most of the respondents achieved middle score (88.3%). The respondents achieving the low score are only 9.3%. The respondents are good enough in Listening and Structure. The scores are 46 and 41, but they are ?weak? in Reading. The score is 39.